Solidão e repressão : "câncer gay" e homossexualidade em Caio Fernando Abreu - Firme, Henrique Albuquerque (2017)
Caio Fernando Abreu’s literature casts in his oeuvre perspectives that are capable of raising sociocultural discussions, transforming itself, various times, in a form of resistence. In this work, we intend to perform an overview of contemporary Brazilian literature, observing the characteristics present in the 1960s to this day. From that point, insert Caio’s fictional pieces, verifying the insertion of his work in the period. The study also proposes to examinate notions of genre and sexuality and how we can read Caio’s opus dialoguing with these theories. In light of this theoretical field, also investigate how AIDS, erroneously vinculated to homossexuality in the beginning of the 1980s, influenced Caio’s literature. For this study, the short stories selected were “Linda, uma história horrível”, from Os dragões não conhecem o paraíso (2013), “Anotações sobre um amor urbano” from Morangos Mofados (2015) and “Terça-feira gorda”, from Ovelhas Negras (2009).